2017
DOI: 10.18298/ijlet.2026
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerine Yönelik Yazma Tutum Ölçeği: Geçerlik ve Güvenirlik Çalışması

Abstract: The aim of this study is to develop a valid and reliable attitude scale towards writing to measure their attitudes towards writing. Scale outline that includes 38 items was performed and validity and reliability studies were done. The study group contained 334 5 th -8 th grade students studying at two different secondary schools in Bursa, Yenişehir. The reliabilty of the scale was analysed in the aspects of construct and content validity. The content validity of the scale was provided by taking the opinions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The scale was developed by Can and Topçuoğlu Ünal (2017) and has 23 items and three subscales. These subscales are named as follows: "relation" subscale of 10 items, "perception" subscale of 6 items and "contribution" subscale of 7 items.…”
Section: The Attitude Scale Towards Writing For Secondary School Studentsmentioning
confidence: 99%
“…The scale was developed by Can and Topçuoğlu Ünal (2017) and has 23 items and three subscales. These subscales are named as follows: "relation" subscale of 10 items, "perception" subscale of 6 items and "contribution" subscale of 7 items.…”
Section: The Attitude Scale Towards Writing For Secondary School Studentsmentioning
confidence: 99%
“…In review of the literature, it is found that there are such studies as writing anxiety scale for secondary school students (Karakuş Tayşi and Taşkın, 2018), writing anxiety scale for those who learn Turkish as a foreign language (Şen and Boylu, 2017;Aytan and Tunçel, 2015;İşcan, 2015), attitude scale (Can and Topçuoğlu Ünal, 2017;Akaydın and Kurnaz, 2015), the adaptation to Turkish of the writing attitude scale (Göçer, 2014), writing disposition scale (İşeri and Ünal, 2010), writing self-efficacy scale (Güneş, Kuşdemir and Bulut, 2017;Şengül, 2013), Turkish adaptation of writing self-efficacy scale (Yılmaz Soylu and Akkoyunlu, 2019). No story writing anxiety scale for secondary school students was encountered in the literature.…”
Section: Story Tellermentioning
confidence: 99%
“…The aim of the Writing Attitude Scale developed by Can and Topçuoğlu Ünal (2017) is to determine the writing attitudes of secondary school students. The scale was prepared in 5-Likert type and consisted of "totally do not agree", "do not agree", "not sure", "agree", "totally agree" for the positive items.…”
Section: Writing Attitude Scalementioning
confidence: 99%